An introduction to medical dance/movement therapy : health care in motion - Goodill, S. (Sherry) (Jessica Kingsley, 2005)
Presenting dance/movement therapy (DMT) as a viable and valuable psychosocial support service for those with a medical illness, Sharon W. Goodill shows how working creatively with the mind/body connection can encourage and enhance the healing process. This book represents the first attempt to compile, synthesize, and publish the work that has been done over recent years in medical DMT. The emerging application of medical DMT is grounded within the context of established viewpoints and theories, such as arts therapies, health psychology and scientific perspectives. As well as examining its theo.